ANALISIS FAKTOR INTERNAL DAN EKSTERNAL YANG MEMPENGARUHI DANA PIHAK KETIGA BANK SYARIAH DI INDONESIA - Bisri, Bisri; Setianingrum, Herlin Widasiswi (Feb Universitas Dirgantara Marsekal Suryadarma, 2019)
This study aims to determine the external and internal factors that affect deposits of Islamic banking. Whereas internal factors in this study is Islamic bank deposits profit sharing and the external factors are interest rate of conventional banks deposits and Indonesia Composite Index (IDX composite). The analysis used is cointegration and error correction model (ECM). As a result, interest rate of conventional banks deposits, Islamic bank deposits profit sharing and IDX composite are stationary at difference 1, then proceed with seeing cointegration that occurs in these variables. The results show cointegration in these variables which is indicated by the ADF value of -3,6951. Furthermore, estimation is done by ECM which gives significant results with ECT values of -0.3326. This shows that in the short and long term, Islamic bank deposits profit sharing, interest rate of conventional banks deposits and IDX composite have a significant effect on the Islamic banks deposits. With the adjusted R-squared value of 0.6032 or 60.32%, it can be seen that the independent variables included in the model are good enough